Determination of Cystic Echinococcosis Seropositivity with Indirect Hemagglutination Technique in Helminthiosis (Annals of Medical Research, 2021)
None
Keywords: Helmint, Indirect Hemagglutination (IHA) Technique, Cross Reactions